Iowa Birdline update, February 25, 1991 notes - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Notes for the Iowa Birdline update for February 25, 1991. Highlights include a Prairie Falcon and an immature Snowy Owl sighted in the same general area. Epson - sheet feed/flatbed